2009
DOI: 10.1097/fbp.0b013e3283313168
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen, raclopride, and naltrexone differentially affect intake of fat and sucrose under limited access conditions

Abstract: Gamma-aminobutyric acid (GABA), dopamine, and opioids are implicated in impulse control, addiction and binge eating. Recent evidence suggests that sucrose alters the effects of GABAergic, dopaminergic, and opioid receptor ligands on consumption of a fatty food in a rat limited-access binge protocol. This study determined the independent effects of fat and sucrose on the efficacy of these ligands under limited-access conditions. Nonfood-deprived male Sprague-Dawley rats had 1 h access to fat (vegetable shorteni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 74 publications
(104 reference statements)
6
73
1
Order By: Relevance
“…The lack of selectivity in the present study is consistent with baclofen's reported ability to alter seeking behavior and consumption of several reinforcers such as normal chow (Ebenezer, 1995), fatty food (Corwin and Wojnicki, 2009), cocaine (Roberts et al, 1996), heroin (Xi and Stein, 1999) and nicotine (Corrigall et al, 2001). Moreover, doses higher than 5 mg/kg can induce sedation in mice (Besheer et al, 2004;Cryan et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…The lack of selectivity in the present study is consistent with baclofen's reported ability to alter seeking behavior and consumption of several reinforcers such as normal chow (Ebenezer, 1995), fatty food (Corwin and Wojnicki, 2009), cocaine (Roberts et al, 1996), heroin (Xi and Stein, 1999) and nicotine (Corrigall et al, 2001). Moreover, doses higher than 5 mg/kg can induce sedation in mice (Besheer et al, 2004;Cryan et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…Avena and colleagues (2009), for instance, reported withdrawallike symptoms in rats bingeing on sugar solutions, but not in rats bingeing on pure fat or fatty foods. In addition, our group has shown that opioid blockade more potently reduced sucrose intake in bingeing rats than in controls; potency differences were not seen in rats consuming fat (Corwin and Wojnicki 2009). These results suggest a unique role for endogenous opioids in sugar bingeing but not in fat bingeing.…”
Section: Effects Of Macronutrients Consumed During the Bingementioning
confidence: 94%
“…We previously reported effects of various peripherally administered pharmacological probes in rats bingeing on sugar solutions and solid fats (Corwin and Wojnicki 2009). Results from these studies indicate differential involvement of dopamine D 2 -like receptors between INT and D rats consuming solid fats but not in INT and D rats consuming sugar solutions.…”
Section: Effects Of Macronutrients Consumed During the Bingementioning
confidence: 95%
See 1 more Smart Citation
“…Further, preclinical studies suggest that overeating sugar produces different addiction-like behaviors compared with overeating fat [5]. There is also a nutrient specificity in the effect that some pharmacological treatments have on reducing overeating [16,17]. Thus, additional knowledge of how different food elements activate brain systems that affect addiction-like behavior will be crucial to developing targeted interventions for people who exhibit signs of 'food addiction'.…”
Section: Food and Addiction -Sugars Fats And Hedonic Overeatingmentioning
confidence: 99%